2017
DOI: 10.1101/222042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hard Limits and Performance Tradeoffs in a Class of Sequestration Feedback Systems

Abstract: A common feature of both biological and man-made systems is the use of feedback to control their behavior. In this paper, we explore a particular model of biomolecular feedback implemented using a sequestration mechanism. This has been demonstrated to implement robust perfect adaption, often referred to as integral control in engineering. Our work generalizes a previous model of the sequestration feedback system and develops an analytical framework for understanding the hard limits, performance tradeoffs, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
57
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(63 citation statements)
references
References 51 publications
(56 reference statements)
6
57
0
Order By: Relevance
“…The field of synthetic biology has focused on the development of novel organisms, devices and systems for the purposes of improving industrial processes [Savage et al, 2008, Clomburg and Gonzalez, 2010, Dunlop et al, 2010, Hemme et al, 2010, Narcross et al, 2016, discovering the principles of natural biological systems [Gardner et al, 2000, Elowitz and Leibler, 2000, Guo et al, 2014, and 20 performing biomolecular computation [Qian et al, 2011, Thubagere Jagadeesh, 2017. Current applications of synthetic biology include industrial fermentation [Georgianna and Mayfield, 2012], toxin detection [McBride et al, 2003, Wang et al, 2009, biosensor development [Hsiao et al, 2016], diagnostics detection [Pardee et al, 2014], materials production [Cherny and Gazit, 2008, Moon et al, 2010, DeLoache et al, 2015, novel protein design [Dahiyat and Mayo, 1996, Arnold, 1998, Kuhlman et al, 2003, and biological computation [Moon et al, 2012, Daniel et al, 2013. The applications and capabilities of synthetic biology are still expanding because it is a relatively novel field.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The field of synthetic biology has focused on the development of novel organisms, devices and systems for the purposes of improving industrial processes [Savage et al, 2008, Clomburg and Gonzalez, 2010, Dunlop et al, 2010, Hemme et al, 2010, Narcross et al, 2016, discovering the principles of natural biological systems [Gardner et al, 2000, Elowitz and Leibler, 2000, Guo et al, 2014, and 20 performing biomolecular computation [Qian et al, 2011, Thubagere Jagadeesh, 2017. Current applications of synthetic biology include industrial fermentation [Georgianna and Mayfield, 2012], toxin detection [McBride et al, 2003, Wang et al, 2009, biosensor development [Hsiao et al, 2016], diagnostics detection [Pardee et al, 2014], materials production [Cherny and Gazit, 2008, Moon et al, 2010, DeLoache et al, 2015, novel protein design [Dahiyat and Mayo, 1996, Arnold, 1998, Kuhlman et al, 2003, and biological computation [Moon et al, 2012, Daniel et al, 2013. The applications and capabilities of synthetic biology are still expanding because it is a relatively novel field.…”
Section: Introductionmentioning
confidence: 99%
“…However, tools and concepts have been developed to ameliorate them [Levine, 2010, Friedland, with no controller species degradation and demonstrated that they can achieve perfect adaptation under certain conditions of stability. Nevertheless, we and others have found the assumption of zero controller species degradation to be too restrictive for the practical implementation of sequestration feedback [Ang et al, 2010, Ren et al, 2017, Qian and Del Vecchio, 2018, Olsman et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reference is set by the external IPTG level that induce AHL synthesis rate so that teh two cell populations achieve a controlled fraction in consortia. The circuit has good tracking accuracy of the reference and robust adaptation because it includes a sequestration-based controller that can be approximated as an integral feedback [25]- [27].…”
Section: Introductionmentioning
confidence: 99%